2015
DOI: 10.1007/978-3-319-17377-1_24
|View full text |Cite
|
Sign up to set email alerts
|

Novelty Detection with One-Class Support Vector Machines

Abstract: In this paper we apply one-class support vector machine (OC-SVM) to identify potential anomalies in financial time series. We view anomalies as deviations from a prevalent distribution which is the main source behind the original signal. We are interested in detecting changes in the distribution and the timing of the occurrence of the anomalous behaviour in financial time series. The algorithm is applied to synthetic and empirical data. We find that our approach detects changes in anomalous behaviour in synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…data, which does not encompass typical time-series data. To address this, [6] and [7] convert time-series data into vectors to enable One-class SVM application.…”
Section: Approaches To Unsupervised Degradation Monitoringmentioning
confidence: 99%
“…data, which does not encompass typical time-series data. To address this, [6] and [7] convert time-series data into vectors to enable One-class SVM application.…”
Section: Approaches To Unsupervised Degradation Monitoringmentioning
confidence: 99%
“…To address this, ref. [ 13 , 14 ] convert time series data into vectors to enable One-class SVM application.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Therefore, we used the STCNN-RN combined with the GACG method to perform comparisons with other benchmark models. We selected the one-class SVM (OC-SVM) [40] and self-organizing maps (SOMs) [41] as the control group.…”
Section: Compare Different Alternative Modelsmentioning
confidence: 99%
“…Shawe-Taylor and Žličar [40] applied the OC-SVM to identify potential anomalies in financial time-series data and to find the distribution and the timing of the occurrence of the anomalous behavior in these data. The experiment results indicated that the OC-SVM detected changes in anomalous behavior in synthetic data sets and in several empirical data sets.…”
Section: Compare Different Alternative Modelsmentioning
confidence: 99%